Microscopic Insights Into the Formation of Methanesulfonic Acid–Methylamine–Ammonia Particles Under Acid-Rich Conditions - Liu, Min; Myllys, Nanna; Han, Yaning; Wang, Zhongteng; Chen, Liang; Liu, Wei; Xu, Jing (Frontiers in Ecology and Evolution, 2022)
Abstract：Understanding the microscopic mechanisms of new particle formation under acid-rich conditions is of significance in atmospheric science. Using quantum chemistry calculations, we investigated the microscopic formation mechanism of methanesulfonic acid (MSA)–methylamine (MA)–ammonia (NH3) clusters. We focused on the binary (MSA)2n-(MA)n and ternary (MSA)3n-(MA)n-(NH3)n, (n = 1−4) systems which contain more acid than base molecules. We found that the lowest-energy isomers in each system possess considerable thermodynamic and dynamic stabilities. In studied cluster structures, all bases are protonated, and they form stable ion pairs with MSA, which contribute to the charge transfer and the stability of clusters. MA and NH3 have a synergistic effect on NPF under acid-rich conditions, and the role of NH3 becomes more remarkable as cluster size increases. The excess of MSA molecules does not only enhance the stability of clusters, but provides potential sites for further growth.